Penerapan Pembelajaran Menggunakan Hand Out dan Peta Konsep untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Sunarti, Sunarti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
The aim of this research was to find out the application of learning using the handout and concept maps to improve the biology learning activities of class VIII students at Suela Junior High School 3 in Academic Year 2015/2016. This type of research was classroom action research consisting of two cycles. Retrieval of learning achievement data using 30 multiple choice evaluation test questions (Î± Cronbach = 0.74) and observation sheets to calculate student learning activities. Analysis of learning outcomes data using individual completeness and classical completeness. So that in getting the average percentage of student learning activities in the cycle of 9.12% with a fairly active category while in the second cycle obtained an average of 12% with the active category. Student learning outcomes using the handout and concept maps for classical completeness in the first cycle amounted to 30% with inactive categories while student learning outcomes using the handout and concept maps for classical completeness in the second cycle were 88% with active categories. Thus it can be said that the application of learning using the handout and concept maps can improve the activities and results of biology learning of class VIII students at 3 Public Schools in Suela 2015/2016 Academic Year